Tool changing 3D printer for rapid prototyping of advanced soft robotic elements. (24th August 2021) - Conrad, Stefan; Speck, Thomas; Tauber, Falk J
Abstract: In the field of soft robotics, pneumatic elements play an important role due to their sensitive and adaptive behavior. Nevertheless, the rapid prototyping of such actuators is still challenging since conventional 3D printers are not designed to fabricate airtight objects or to specify their bending behavior by combining materials of different stiffness. In order to address this challenge, a tool changing multi-material 3D printer has been constructed, which can be equipped with various print-heads fitted to the specific application. By alternately processing filaments with varying mechanical properties, a series of pneumatic elements was produced. The actuators were printed in thermoplastic polyurethane with shore hardness A70 for flexible parts and D65 for stiff parts. A novel procedure for the feature adaptation of the flow rate allowed the fabrication of vertically printed flexible membranes with a thickness of just 500 μ m. This way the bending and expanding printed structures can all be actuated with a pressure of 100 kPa or less. Furthermore, a new kind of generic actuator that is customizable to specific tasks and can perform complex motion behavior was designed. All together, these actuators demonstrate the high potential of the developed platform for further research on and production of soft robotic elements and complex pressurized systems.